Polarization response characteristics of structure gradient MWCNTs/PDMS under vibration - Feigao Fan; Yihao Liu; Mengzhou Chang; Lulu Li; Kai Guo (Results in Physics)
Low electromechanical coupling coefficient has become the key problem restricting the application of flexible electronic components. In this paper, structure gradient MWCNTs/PDMS composites have been prepared, the electromechanical properties have been investigated by cantilever beam experiment. Numerical simulations based on flexoelectric theory have been conducted to investigate the relationship between polarization strengths, voltage distributions and strain gradients. The results show that polarization voltage U show sinusoidal-like periodic decay behavior. Generally, U of linear structure gradient cantilever beam (98.6 mV) are larger than homogeneous structure (56.3 mV, 1 wt%), symmetry and anti-symmetry structure gradient. The polarization strength P of linear structural gradient cantilever beam is in the range of −600 ∼ 600 pC/m2. There exists an out of phase relationship between P and displacement. The flexoelectric coefficients of homogeneous structure MWCNTs/PDMS are generally about 10-10C·m−1. However, that of linear structure gradient MWCNTs/PDMS reaches 10-8C·m−1. The structure gradient MWCNTs/PDMS composites with high electromechanical coupling coefficients can be used in the field of flexible intelligent sensing in the future.